Recurrent Stroke in a Young Adult due to Section Antiphospholipid Antibody Syndrome-A Case Report - Siraveni Thirupathi; Dinesh Ragav; Nasreen Begum (Journal of Clinical and Diagnostic Research, 2019)
Antiphospholipid Syndrome (APS) is an autoimmune disease characterised by arterial thrombosis, venous thromboembolic complications, mild to moderate thrombocytopenia and/or pregnancy morbidities in the presence of persistently positive levels of antiphospholipid antibodies (aPL) such as Lupus Anticoagulant (LA), anticardiolipin (aCL), and anti-β2 -glycoprotein-I (aβ2 GPI) antibodies. Many mechanisms create a prothrombotic state, it is prone to complication like abortions, preterm deliveries, foetal loss, cerebral stroke, acute coronary syndrome, venous thromboembolic and peripheral vascular occlusive disorders, intracerebral haemorrhage, encephalopathy and infections. Here, the case of a 42-year-old female is being reported, who was diagnosed with APS, treated with warfarin. The available knowledge about this disease and its relevance to the symptoms of the patient is also summarised.